A single method for detecting 11 organophosphate pesticides in human plasma and breastmilk using GC-FPD - Warangkana Naksen (2018)
© 2016 Elsevier B.V. Organophosphate (OP) pesticides are widely used for crop protection in many countries including Thailand. Aside from causing environmental contamination, they affect human health especially by over-stimulating of the neurotransmission system. OP pesticides, as with other non-persistent pesticides, degrade quickly in the environment as well as are metabolized quite rapidly in humans. Assessing human exposures to these compounds requires analytical methods that are sensitive, robust, and most importantly, suitable for specific laboratory settings. The aim of this study was to develop and validate an analytical method for measuring 11 OP pesticide residues in human plasma and breast milk. Analytes in both plasma and breast milk samples were extracted with acetone and methylene chloride, cleaned-up using aminopropyl solid phase extraction cartridges, and analyzed by gas chromatography with flame photometric detection. The optimized method exhibited good linearity, with the coefficients of determination of 0.996-0.999 and <7% error about the slope. Extraction recoveries from spiked plasma and breast milk samples at low and medium concentrations (0.8-5.0 and 1.6-10 ng mL-1, respectively) ranged from 59.4% (ethion) to 94.0% (chlorpyrifos). Intra-batch and inter-batch precisions ranged from 2.3-18.9% and 5.8-19.5%, respectively. Method detection limits of plasma and breast milk ranged from 0.18-1.36 and 0.09-2.66 ng mL-1, respectively. We analyzed 63 plasma and 30 breastmilk samples collected from farmworkers in Chiang Mai Province to determine the suitability of this method for occupational exposure assessment. Of the 11 pesticides measured, seven were detected in plasma samples and five were detected in breast milk samples. Mass spectrometry was used to confirm results. Overall, this method is rapid and reliable. It offers the laboratories with limited access to mass spectrometry a capacity to investigate levels OP pesticides in plasma and breastmilk in those occupationally exposed for health risk assessment.